Influence of solvents on the enhancement of thermophysical properties and stability of multi-walled carbon nanotubes nanofluid - Bakthavatchalam, B. (Institute of Physics Publishing, 2020)
Multi-walled carbon nanotubes (MWCNTs) are a contemporary class of nanoparticles that have a prominent thermal, electrical and mechanical properties. There have been numerous studies on the enhancement of thermophysical properties of nanofluids. However, there is only limited research on thermal and stability analysis of MWCNT nanofluids with various kinds of solvents or base fluids, namely propylene glycol, ethanol, ethylene glycol, polyethylene glycol, methanol and water. This paper reports the enhancement of thermophysical properties and stability of MWCNTs with six different base fluids in the presence of sodium dodecyl benzene sulfonate surfactant with a mass concentration of 0.5 wt. Thermal and dispersion stabilities were determined using a thermogravimetric analyzer (TGA) and Zeta potential, along with a visual inspection method to evaluate the agglomeration or sedimentation of MWCNT nanoparticles over a period of one month. Ultraviolet-visible spectroscopy and Fourier transform infrared spectroscopy were utilized to identify the molecular components and light absorption of the formulated nanofluids at their maximum wavenumber (4500 cm-1) and wavelength (800 nm). In addition, thermophysical properties such as thermal conductivity, specific heat capacity, viscosity and density with a peak temperature of 200 C were also experimentally evaluated. The TGA results illustrated that MWCNT/ethylene glycol nanofluid achieved maximum thermal stability at 140 C and it revealed a maximum zeta potential value of -61.8 mV. Thus, ethylene glycol solution was found to be the best base liquid to homogenize with MWCNTs for acquiring an enhanced thermophysical property and a long-term stability. Â© 2020 IOP Publishing Ltd.